Research on the Muzzle Blast Flow with Gas-Particle Mixtures Based on Eulerian-Eulerian Approach. (16th July 2015) - Zhuo, C.-F.; Yao, W.-J.; Wu, X.-S.; Feng, F.; Xu, P.
Abstract : The issue on the muzzle blast flow with gas-particle mixtures was numerically investigated in this paper. The propellant gas in the cannon was assumed to be gas-particle mixtures consisting of a variety of gaseous species and particles. The model made use of the Eulerian-Eulerican approach, where the particle were modeled as a second fluid with parameters like bulk density, velocity and temperature, interacting with the gas flow. A high-resolution upwind scheme(AUSMPW+) and detailed reaction kinetics model were employed to solve the chemical non-equilibrium Euler equations for gas phase. The Euler equations for particle phase were solved by MacCormack scheme. The particle diameter and the mass fraction of particle were tested to show their effects on the development process of muzzle blast flow with gas-particle mixtures. The distribution of the main flow parameters of both gas and particle were obtained at different time intervals. The results show the evolution of the muzzle blast flow with gas-particle mixtures and demonstrate the effects of key parameter on the flow field of the gas-particle flow. This paper is a significant investigation for understanding the muzzle blast flow with gas-particle mixtures, which can provide valuable reference for the research on the muzzle blast flow.